Numerical Modelling and Simulation of Membrane-Based Extraction of Copper (Ii) Using Hollow Fiber Contactors - Romero-Figueroa, J (Desalination Publications, 2017)
This work describes the mathematical modelling and numerical simulation of a hollow fiber membrane contactor for copper (II) extraction from aqueous solutions with 1,1,1-trifluoro-2,4-pentanedione commonly known as TFA diluted in n-decanol. Model was developed for convection–diffusion mass and momentum transfer using continuity and Navier–Stokes equations. Model equations were solved using a computational fluid dynamics code, and results were validated with experimental data. After validation of model, simulation was performed to check the effects of hydrodynamics conditions on contactor performance. 49% of copper (II) was extracted from aqueous solution for feed flow rate of 8.3 × 10–7 m3.s–1, and for partition coefficient equals to 1. However, simulation results indicated that extraction could be greatly improved by decreasing feed flow and increasing partition coefficient. Simulation was also run to study the distribution profiles of copper (II) concentration, flux and velocity in 2-D. © 2017 Desalination Publications. All rights reserved.